Post-Cold War Great Power Strategic Engagements: United States – China - Russia - Putri, Faradillah Isnaeni; Pedrason, Rodon; Inkiriwang, Frega Ferdinand Wenas; Andriyanto, Kristoforus Evan; Arum, Dyah Sekar (Formosa Journal of Multidisciplinary Research, 2024)
The post-Cold War period witnessed the evolution of Great Power Strategic Engagements (GPSE) among the United States, China, and Russia, characterized by cooperation, competition, and complex interactions. These engagements impact global stability through military, economic, and diplomatic spheres. Strategic competition, particularly influenced by economic and technological ambitions, has shaped policies and alliances. This research employs a qualitative approach, analyzing literature to understand how GPSE and Great Power Competition (GPC) interplay affects international order and defense strategies, emphasizing cooperation potential and conflict risks. The study underscores the delicate balance between rivalry and collaboration.